2019
DOI: 10.1186/s40748-019-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early versus delayed cord clamping in neonate on heart rate, breathing and oxygen saturation during first 10 minutes of birth - randomized clinical trial

Abstract: Background Delayed cord clamping (DCC) after 180 s reduces iron deficiency up to 8 months of infancy compared to babies who received Early Cord Clamping (ECC) at less than 60 s. Experimentally DCC has shown to improve cardio-vascular stability. To evaluate the effect of delayed (≥180 s) group versus early (≤60 s) cord clamping group on peripheral blood oxygenation and heart rate up to 10 min after birth on term and late preterm infants. Methods We conducted a single cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
5
38
0
1
Order By: Relevance
“…Another study from 2019 found higher levels of Oxygen in babies with delayed cord clamping than in those who had early cord clamping, in addition to slower heart beat and higher Apgar scores (12). Studies have not found an elevated risk of postpartum haemorrhage of the mothers, and the bene ts to the baby is equally high or higher when delivered by Caesarean section (11,12,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from 2019 found higher levels of Oxygen in babies with delayed cord clamping than in those who had early cord clamping, in addition to slower heart beat and higher Apgar scores (12). Studies have not found an elevated risk of postpartum haemorrhage of the mothers, and the bene ts to the baby is equally high or higher when delivered by Caesarean section (11,12,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed description of newborn procedures such as delayed cord clamping, suction, kangaroo care and early initiation of breastfeeding are included, thus our interview guide focused on these stages connected to birth: Monitoring of labour using partograms gives a better indication of labour progress for easy recognition of early complications (9,10). Delayed cord clamping (DCC) refers to clamping later than 60 seconds after birth or when cord pulsation has ceased, contrary to early cord clamping (ECC) which take place within one minute after birth (11,12). Suction of newborns is a method used to clear secretions from the oropharynx and nasopharynx through the application of negative pressure via a suction catheter or bulb syringe, and is not recommended for uncomplicated births (13).…”
mentioning
confidence: 99%
“…Outcomes of the NepCord trial have previously been reported. 9,11 The primary outcome was the haemoglobin levels at 8 months of age, and the secondary outcomes were the ferritin levels at eight and 12 months and the haemoglobin level and neurodevelopment at 12 months of age. The results showed a reduction in anaemia levels in the delayed group at eight and 12 months of age.…”
Section: Outcomementioning
confidence: 99%
“…It has also been reported that around 30%‐40% of blood volume, roughly 25‐30 mL/kg, is transfused if early cord clamping is avoided . Sustaining cord circulation for 3 minutes can improve oxygen saturation and Apgar scores in spontaneously breathing babies . It can provide sufficient amounts of iron to reduce iron deficiency for up to 8 months and reduce anaemia for up to 12 months after birth .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation